Lame cows have a subdued hypothalamus-pituitary axis as revealed by LH release in response to exogenous endocrine challenges - SOOD, PANKAJ; NANDA, A S; NANDA, A S; PRAKASH, B S (The Indian Journal of Animal Sciences, 2019)
Lameness is a serious concern in cows due to its multilevel effects and increasing incidences. The ability of anterior pituitary and hypothalamus to release LH, a prime reproductive hormone, is unknown in lame cows. Our study tested this ability by exogenous endocrine challenge using Buserelin acetate (GnRH analogue) and estradiol valerate (EV). The study included moderately lame (L; n=7) either cyclic (LC; n=3) or anestrus (LA; n=4); and normal cyclic, non–lame (NL; n=5) cows. Progesterone blocks LH release, so it was lowered by injecting PG in cyclic cows. After 14 h, all cows were given a walk for 5 min and immediately thereafter injected with 0.008 mg GnRH and 4 h later with 1 mg of EV. Blood plasma progesterone, cortisol and LH were quantified, periodically. There was a significant delay in the onset (105.0 vs 75.0±7.0 vs 54.0±9.0 min) and duration (22.5±5.3 vs 80.0±10.8 vs 117.0±2.7 min) of LH surge in LA vs LC vs NL cows; the surge was absent in two LA cows. The altered LH profile was attributed to a 3 fold (in L) vs 1.6 fold (in NL) rise in cortisol. LH released (ng/ml) in response to EV was also low in LA (31.5±2.4) and LC (69.9±7.2) than NL (79.2±7.0) cows. In conclusion, lame cows subjected to walk exhibited reduced pituitary response to release LH following exogenous GnRH as also a reduced ability of hypothalamus to stimulate LH release in response to exogenous estradiol.